2013
DOI: 10.1128/aem.02200-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hemolysin Genes and Comparison of ehxA Subtype Patterns in Shiga Toxin-Producing Escherichia coli (STEC) and Non-STEC Strains from Clinical, Food, and Animal Sources

Abstract: c Shiga toxin-producing Escherichia coli (STEC) belonging to certain serogroups (e.g., O157 and O26) can cause serious conditions like hemolytic-uremic syndrome (HUS), but other strains might be equally pathogenic. While virulence factors, like stx and eae, have been well studied, little is known about the prevalence of the E. coli hemolysin genes (hlyA, ehxA, e-hlyA, and sheA) in association with these factors. Hemolysins are potential virulence factors, and ehxA and hlyA have been associated with human illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 76 publications
(103 reference statements)
10
45
2
Order By: Relevance
“…These include, for example, the enterohemolysin, encoded by the ehxA gene, which is linked to cytotoxic effects on endothelial cells (24), the enteroaggregative E. coli (EAEC) heat-stable enterotoxin, encoded by the astA gene (25), and the alpha-hemolysin, encoded by the hlyA gene (26).…”
mentioning
confidence: 99%
“…These include, for example, the enterohemolysin, encoded by the ehxA gene, which is linked to cytotoxic effects on endothelial cells (24), the enteroaggregative E. coli (EAEC) heat-stable enterotoxin, encoded by the astA gene (25), and the alpha-hemolysin, encoded by the hlyA gene (26).…”
mentioning
confidence: 99%
“…ehxA subtypes of plasmids sequenced in this study were previously identified by PCR-RFLP (32,41). ehxA subtypes of previously sequenced E. coli plasmids used for comparative analysis in the current study (Table 1) were identified using the CLC Genomics Workbench restriction site analysis tool.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains used in this study are listed in Table 1. Strains CFSAN004176 to CFSAN004181 have been described previously as 03-3375, 05-3014, 06-00048, 08-00022, 09-00049, and USMARC_GB_STEC_089, respectively (32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations